Edugame “Etam-Tainment” Pembelajaran Bahasa Kutai dengan Shuffle Random dan Agen Cerdas - Sefty Wijayanti; Asep Nurhuda; Reza Andrea (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
The research entitled Educational Game (Edugame) "Etam-tainment" is a research development of Puzzle Game type, designed to hone memory in the form of language. In this game, players must arrange letters in random and create a word in Kutai language. Artificial Intelligence (AI) technology will also be applied to this research. Using the Finite State Machine model method, this game will have game agent character that will accompany a child to play like a teacher. Game agent in the form of virtual teacher can give a sad and happy expression accordingly from the game environment. The results of this study make this edugame become more interesting and interactive to children. Game agent AI will accompany child in this game is like teacher.